Identifikasi Arsitektur Kolonial Pada Bangunan Peninggalan Belanda Di Kabupaten Bireuen (Pendopo Bireuen, Balai Desa Kecamatan Gandapura Dan Rumah Uleebalang Peusangan) - Riskia, Rina; Dafrina, Armelia; Olivia, Sisca (Rifa'Institute, 2023)
Colonial architecture is architecture that emerged when Indonesia was colonized by the Dutch. Colonial architecture is more prominent than the Dutch architectural style because the Netherlands was the country that colonized Indonesia the longest, so the Dutch government had time to build several buildings in a typical Dutch style, especially government buildings. Bireuen became one of the areas controlled by the Dutch, where the Dutch had built several buildings in a typical Dutch style, especially government buildings. This study aims to identify and examine the characteristics of Dutch colonial architecture in Dutch heritage buildings in Bireuen Regency. This research is also expected to strengthen the identity of Bireuen Regency as one of the regencies in the Indonesian region which is rich in historical value and can become a learning medium for present and future generations.The results of the analysis show that the three research objects have the characteristics of Dutch colonial architecture in accordance with the construction period of the three buildings used as the research object. There are eight characteristics of colonial architecture that exist in the Bireuen Pendopo building, namely geveltoppen, cripedoma, entrance with two doors, symmetrical facade, wooden framed windows, wood wall materials, metal material decoration, and decoration on the body of the building. In the Gandapura Village Hall building there are seven characteristics of colonial architecture namely gevel, geveltoppen, cripedoman, entrance with two doors, symmetrical facade, wooden framed windows, wood wall materials. Whereas in the Uleebalang Peusangan house there is a cripedoman, an entrance with two doors, a symmetrical facade, windows with wooden frames.